APPLICATION OF THE INDEX CARD MATCH MODEL TO IMPROVE THE LEARNING OUTCOMES OF THE MORAL BELIEFS OF GRADE VII JUNIOR HIGH SCHOOL STUDENTS TQ MUADZ BIN JABBAL - Wa Ode Hariati; Muh. Yusuf T; Muh. Rapi (Tadbir: Jurnal Manajemen Pendidikan Islam, 2025)
This classroom action research addressed the low learning outcomes and passive participation of Grade VII students in Akidah Akhlak at SMP TQ Muadz Bin Jabbal, which were initially hindered by conventional, teacher-centred methods. The Index Card Match (ICM) model was implemented in the social constructivist learning theory to create interactive and collaborative learning. The study aimed to improve the process and learning outcomes, specifically targeting increased mastery and active involvement in each cycle. Employing the Kemmis & McTaggart PTK model across two cycles, the research involved the subject teacher and all students in the class. Data were collected through observation, tests, interviews, and documentation, then analysed using descriptive quantitative and qualitative approaches. Findings revealed a progressive improvement from pre-cycle to the second cycle, with significant growth in mastery levels, engagement, and collaborative skills. Students became more confident in expressing ideas, while the teacher became a facilitator. These results affirm that ICM can enhance understanding and moral values simultaneously. This research contributes to classroom practice improvement, teacher professional development, and strengthens the evidence base for cooperative, game-based learning models.